2013
DOI: 10.1063/1.4833250
|View full text |Cite
|
Sign up to set email alerts
|

Phonon and thermal properties of exfoliated TaSe2 thin films

Abstract: We report on the phonon and thermal properties of thin films of tantalum diselenide (2H-TaSe 2 ) obtained via the "graphene-like" mechanical exfoliation of crystals grown by chemical vapor transport. The ratio of the intensities of the Raman peak from the Si substrate and the E 2g peak of TaSe 2 presents a convenient metric for quantifying film thickness. The temperature coefficients for two main Raman peaks, A 1g and E 2g , are -0.013 and -0.0097 cm -1 / o C, respectively. The Raman optothermal measurements i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 39 publications
1
74
0
2
Order By: Relevance
“…Deposition of products in the form of single crystals is driven by a temperature gradient between the source and the growth regions [49]. Bulk CDW materials such as 1T-VSe2 [50], 1T-TaSe2 [28], 2H-TaSe2 [5,51] and 2H-NbSe2 [52] have been reported by the CVT method in recent years. For synthesis of 2D CDW materials, recently, J. Wang et al reported controlled synthesis of two-dimensional 1T-TiSe2 on sapphire substrates with sub-10-nm thickness [53] (Figure 5).…”
Section: Chemical Vapor Transportmentioning
confidence: 99%
“…Deposition of products in the form of single crystals is driven by a temperature gradient between the source and the growth regions [49]. Bulk CDW materials such as 1T-VSe2 [50], 1T-TaSe2 [28], 2H-TaSe2 [5,51] and 2H-NbSe2 [52] have been reported by the CVT method in recent years. For synthesis of 2D CDW materials, recently, J. Wang et al reported controlled synthesis of two-dimensional 1T-TiSe2 on sapphire substrates with sub-10-nm thickness [53] (Figure 5).…”
Section: Chemical Vapor Transportmentioning
confidence: 99%
“…Recent advances in the exfoliation and growth of quasi two-dimensional (2D) layered materialsreferred to as van der Waals materials -have resulted in a surge of interest to their possible device applications [5][6][7][8]. One of the most promising materials among the layered transitionmetal dichalcogenides (TMD) is MoS 2 [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above properties, S and F dopants are being explored to make graphene magnetic [10,[52][53][54][55], while N dopants are expected to provide much higher enhancements in quantum capacitance without compromising electrical conductivity [28]. Similar to Bi 2 Te 3 , defects in other layered systems such as SnSe and TaSe 2 could be engineered to achieve better thermoelectric performance [56][57][58][59][60][61][62]. Although this chapter presented only some examples of defects in 2D materials, the same concepts also hold true for other 2D materials such as MoS 2 , WS 2 , and BN.…”
Section: Discussionmentioning
confidence: 99%